Lobi Israel dalam Kebijakan Luar Negeri Amerika Serikat ke Timur Tengah - Iqbal Ramadhan (Intermestic: Journal of International Studies, 2017)
This research was conducted based on a research problem that discussed about the role of pro-Israeli lobby groups which dominated US foreign policy in the Middle East. The research focused on US foreign policy during George W. Bush’s regime. At that time, US foreign policy in the Middle East was giving a favorable outcome for Israeli government. The researcher used qualitative method and case study analysis in this research. The concept and theory harnessed foreign policy concept from Lovell and pluralist lobby theory. The result of this research was Israel’s lobby groups were an input in decision making process as an interest. The lobby played its role as the main source of information which were used by US government as a foreign policy domestic input. They had financial and political power that were able to lobby both directly and indirectly. Keyword: Foreign policy, decision making process, Israel’s lobby